The Circulatory System in an Electromagnetic Field - Savenko, Elena; Belov, Alexander (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
The article deals with the interaction of two electromagnetic fields: the intrinsic electromagnetic field of the elements of circulatory system and the external electromagnetic field of environment. A model of the circulatory system is proposed that allows for a systematic assessment of the impact of electromagnetic fields on the cardiovascular system. The model is based on the biophysical and bioelectrical properties of the elements of the cardiovascular system and the central nervous system. The article considers issues related to the behavior of the vessels of the arterial part of the vascular bed: the capillary network, arterioles and large arteries in an electromagnetic field. The dynamics of myocardial behavior in two phases is clearly illustrated using a two-circuit electrical circuit. The change in the dynamics of the state of an elementary section of the vascular bed over time is estimated using a system of equations based on Hooke's law. The possible mechanism of human behavioral character in unfavorable environmental conditions is analyzed based on the principle of adequate design, which is presented in the diagram of the step-by-step impact of the external environment and its influence on the behavior of the cardiovascular system depending on the intensity of the impact.